ISLAMIC WEALTH MANAGEMENT AND FINANCIAL ADVISORY : A STUDY GUIDE - Ruslinda Sulaiman, author; Lahsasna, Ahcene, author; Maznita Mokhtar, author (Kuala Lumpur : IBFIM, 2014)
Includes bibliographical references and index